Best Answer

X squared is not an inverse function; it is a quadratic function.

Q: Why is x squared a inverse function?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

square root of x/pi

if f(x) = 4x, then the inverse function g(x) = x/4

A function that, given X, will produce Y has an inverse function that will take Y and produce X. More formally:If f(x)=y, then f-1(y)=xWhere f-1() denotes the inverse function of f()

The inverse of the function y = 9x is x/9.

1

Related questions

XX or X*X, can be written as X squared. The inverse of a function "sort of cancels it out". I know the inverse of a square is the square root. Since we need the inverse of X squared, it's inverse is the square root of X. sqrt(x)

square root of x/pi

x squared plus 5

In order for a fourth degree function to have an inverse function, its domain must be restricted. Otherwise the inverse function will not pass the vertical-line test.Ex.f(x) = x^4 (x>0), the original functionf-1(x) = x ^ (1/4), the inverse

Simply stated, the inverse of a function is a function where the variables are reversed. If you have a function f(x) = y, the inverse is denoted as f-1(y) = x. Examples: y=x+3 Inverse is x=y+3, or y=x-3 y=2x+5 Inverse is x=2y+5, or y=(x-5)/2

2

Answer: The difference between the square root of x and squared is either x or -x. Answer: The square root is the inverse function of the square function. That means that it's basically the opposite. Asking for the square root of "x" is like asking "what number must I square to get 'x'".

if f(x) = 4x, then the inverse function g(x) = x/4

0

No. A simple example of this is y = x2; the inverse is x = y2, which is not a function.

In general the function and it inverse are not the same and do not have the same graph. If we look at a special function f(x)=x, it is equal to its inverse and the graph is the same. Think of the inverse of a function as changing all the x's to y's and vice versa. Well, in the function f(x)=x, all the x's are already y's and vice versa so it is its own invese.

A function that, given X, will produce Y has an inverse function that will take Y and produce X. More formally:If f(x)=y, then f-1(y)=xWhere f-1() denotes the inverse function of f()